RELEVANSI QUR’AN SURAH AR-RAD AYAT 8 PADA FISIKA MATERI PENGUKURAN - Armando Bachtiar, Armando; Sholehudin, Sholehudin; Mardiana , Mardiana Ningsih; Tsania Sabilahaq, Tsania; Budi Johan, Budi (IAIN Ambon, 2024)
Abstract: This research explores the connection between the concept of measurement in physics and the Quranic teachings regarding Allah's precise knowledge of all things. This research employing a qualitative approach with a literature review method, this study analyzes Surah Ar-Ra'd verse 8 of the Quran and physics literature related to measurement in depth. The primary data source is the Quran, specifically the aforementioned verse, which is examined alongside physics literature. The findings reveal that the precision and accuracy inherent in the physics concept of measurement resonate with the verse's explanation that all things have an exact measure in Allah's knowledge. The principles of precision in physical measurements, such as using accurate instruments and careful procedures, mirror the concept that everything has a precise measure in Allah's knowledge. This finding strengthens the argument that scientific knowledge and Islamic teachings are not separate domains but rather complementary and mutually supportive. Consequently, integrating these two realms in the learning process can assist students in comprehending the complementary relationship between science and the spiritual values of religion. Abstrak: Penelitian ini mengeksplorasi keterkaitan antara konsep pengukuran dalam fisika dengan ajaran Al-Qur'an mengenai segala sesuatu yang terukur secara presisi di sisi Allah SWT. Penelitian ini menggunakan pendekatan kualitatif dengan metode kajian pustaka, kajian ini menganalisis Surah Ar-Ra'd ayat 8 Al-Qur'an dan literatur fisika terkait pengukuran secara mendalam. Sumber data utama adalah Al-Qur'an, khususnya ayat tersebut, yang dikaji bersama literatur fisika. Hasil penelitian menunjukkan bahwa ketelitian dan keakuratan dalam konsep pengukuran fisika memiliki keselarasan dengan penjelasan ayat tentang pengetahuan Allah atas segala sesuatu yang terukur dengan tepat. Prinsip ketelitian dalam pengukuran fisika, seperti menggunakan alat ukur yang akurat dan prosedur yang cermat, merupakan cerminan dari konsep bahwa segala sesuatu memiliki ukuran yang tepat dalam pengetahuan Allah. Temuan ini memperkuat argumen bahwa ilmu pengetahuan dan ajaran agama Islam bukan dua hal yang terpisah, melainkan saling mendukung dan melengkapi satu sama lain. Dengan demikian, integrasi keduanya dalam proses pembelajaran dapat membantu memahami hubungan saling melengkapi antara sains dan nilai-nilai spiritual agama.